Mere Christianity : a revised and amplified edition, with a new introduction, of the three books, Broadcast talks, Christian behaviour, and Beyond personality - Lewis, C. S. (Clive Staples), 1898-1963. (San Francisco : HarperSanFrancisco, 2001)
This book is one of the most popular introductions to Christian faith ever written. Mere Christianity has sold millions of copies worldwide. The book brings together C.S. Lewis's legendary broadcast talks of the war years, talks in which he set out simply to "explain and defend the belief that has been common to nearly all Christians at all times." Rejecting the boundaries that divide Christianity's many denominations, Lewis provides an unequaled opportunity for believers and nonbelievers alike to hear a powerful, rational case for the Christian faith. It is a collection of scintillating brilliance that remains strikingly fresh for the modern reader and at the same time confirms C.S. Lewis's reputation as one of the leading writers and thinkers of our age. - Jacket flap.
This volume discusses the essence of Christian faith and the doctrine of the Trinity. It is a discussion of Christian belief that rejects the boundaries that divide Christianity's many denominations. The author finds a common ground on which all Christians can stand together, and provides an unequaled opportunity for believers and nonbelievers alike to hear a powerful, rational case for their faith.
Book I. Right and wrong as a clue to the meaning of the universe. The Law of Human Nature ; Some objections ; The reality of the Law ; What lies behind the Law ; We have cause to be uneasy -- Book II. What Christians believe. The rival conceptions of God ; The invasion ; The shocking alternative ; The perfect penitent ; The practical conclusion -- Book III. Christian behaviour. The three parts of morality ; The "cardinal virtues" ; Social morality ; Morality and psychoanalysis ; Sexual morality ; Christian marriage ; Forgiveness ; The great sin ; Charity ; Hope ; Faith ; Faith [continued] -- Book IV. Beyond personality: or, First steps in the doctrine of the Trinity. Making and begetting ; The three-personal God ; Time and beyond time ; Good infection ; The obstinate toy soldiers ; Two notes ; Let's pretend ; Is Christianity hard or easy? ; Counting the cost ; Nice people or new men ; The new men.
Includes bibliographical references.
Originally published: London : G. Bles, 1952.
Keywords: Theology, Doctrinal -- Popular works; Apologetics; Christian ethics -- Anglican authors; Theology, Doctrinal -- Popular works; Apologetics; Christian ethics -- Anglican authors; Apologetics; Christian ethics -- Anglican authors; Theology, Doctrinal; Popular works